Examination of sports science faculty students’ attitudes towards online learning by different variables - Hulusi Böke; Şakir Tüfekçi (Physical Education of Students)
Background and Study Aim. In distance education, students’ attitudes towards this method gain importance in the process. The aim of this research is to examine the impact of coronavirus anxiety, academic self-sufficiency and life satisfaction levels of students in the faculty of sports sciences over their attitudes towards online learning.